The humanities and temporal transgression. Remarks not only for the pandemic times - Lemann, Natalia (Język(i) w czasie i przestrzeni, 2021)
This article attempts to diagnose endeavours facing the post-pandemic humanities, and it provides an overview of humanities and its capability for temporal transgression. The author discusses philosophical theses about the nature of time and temporal experience (born within Existentialism), which is the starting point for presentation of the temporal transgression’s challenge present in the humanities, in terms of labour, activity, and anagogy. A brief review of relevant philosophical stances allows for proposing a term ‘tender humanist’ (modelled after ‘tender narrator’ by Olga Tokarczuk). The author believes that this term perfectly reflects a methodological attitude consisting of empathetic and sympathetic opening on messages and meanings flowing from literature, both that written in the past, as well as science-fiction literature, designing the future.